Methemoglobinemia as biomarker and precursor of brain capillary oxidative damage link to ferric iron accumulation and originator of neurodegenerative diseases. Issue 5 (2017) - Mohorovic, Lucijan; Lavezzi, Anna M.; Jonjic, Nives; Stifter, Sanja; Perry, George; Malatestinic, Djulija
No abstract available